ChemInform Abstract: Biological and Pharmacological Activities of Amaryllidaceae Alkaloids. Issue 18 (May 2015) - He, Maomao; Qu, Chunrong; Gao, Oude; Hu, Xianming; Hong, Xuechuan
Abstract Review: data since 2005; 81 refs.